1964
DOI: 10.1002/jsfa.2740150304
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term storage of wheat

Abstract: She reported that this fraction decreased during storage and also ' when the fruit is left to mature on the tree '. In the present results there is a similar trend, which is particularly noticeable with the apples from D 3. The first two picks have a residue of 26°/0 which falls to I . S~~ in 4 weeks, and then remains more or less constant.If the well-known major changes in starch and acid are ignored, and also the marginal changes in some organic substances, it appears that the only constituents investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1965
1965
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Although stored grain is considered to be dormant, endogenous germinative enzymes probably still act on the storage lipids and carbohydrates to produce these breakdown products. The nutrient losses observed by Pixton et al (1964) were so small that no detectable change in the metabolisable energy (ME) concentrations of the stored wheat samples would be expected in poultry-based bioassays. However, empirical measures of ME of wheat samples stored for different lengths of time have given conflicting results.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although stored grain is considered to be dormant, endogenous germinative enzymes probably still act on the storage lipids and carbohydrates to produce these breakdown products. The nutrient losses observed by Pixton et al (1964) were so small that no detectable change in the metabolisable energy (ME) concentrations of the stored wheat samples would be expected in poultry-based bioassays. However, empirical measures of ME of wheat samples stored for different lengths of time have given conflicting results.…”
Section: Introductionmentioning
confidence: 98%
“…Long-term studies on the chemical composition of stored wheat samples have found no changes in the protein content of the samples but small increases in the contents of free fatty acids, maltose and sucrose (Pixton et al, 1964). Although stored grain is considered to be dormant, endogenous germinative enzymes probably still act on the storage lipids and carbohydrates to produce these breakdown products.…”
Section: Introductionmentioning
confidence: 98%
“…Cereal grains undergo pronounced biochemical changes during storage. The moisture content of grains, storage form, storage time and temperature have been shown to exert significant changes in the acidity and quality of protein, which significantly affect rheological properties of dough made from stored wheat (Pixton & Hill, 1967; Rehman & Shah, 1999; Yu, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The viability of samples of wheat and rapeseed were determined before the previous experiment, and again on samples from each experimental condition at the end of each experiment, using the method described by Pixton et aZ., 5 except that the seeds were kept at 20°C. There was no loss of total germination at the two lower humidities, in samples that had adsorbed, but there was some loss during desorption especially at atmospheric pressure ( Table 2).…”
Section: The Effect Of Reduced Pressure On Viabilitymentioning
confidence: 99%